Financial Performance of Banking Companies on the Indonesian Stock Exchange - Dewi, Ida Ayu Satwika; Mariati, Ni Putu Ayu Mirah; Sunarwijaya, I Ketut Sunarwijaya (Philippine Social Science Journal, 2025)
This study investigates the determinants of financial performance (ROA) across 35 banking companies listed on the Indonesia Stock Exchange from 2019 to 2022. The analysis reveals that independent commissioners, the board of directors, and company size positively influence performance through improved governance and efficiency, while institutional and managerial ownership show no significant effect. These findings offer vital insights for stakeholders regarding risk and strategy, suggesting future research should expand the scope to include variables such as audit committees, intellectual capital, and leverage across broader industry samples.